Terrorist groups online networking tactics: Why Twitter Magnetize the youth of Saudi Arabia? - Zanuddin, Hasmah; Alyousef, Yazeed (Science Publishing Corporation, 2018)
In July 2013, the European Parliament distinguished Wahhabism as the fundamental wellspring of worldwide fear mongering, but then the Grand Mufti of Saudi Arabia, censuring IS in the most grounded terms, has demanded that "the thoughts of fanaticism, radicalism and psychological warfare don't have a place with Islam in any capacity". Different individuals from the Saudi decision class, be that as it may, look all the more sympathetic on the development, commending its staunch restriction to Shiaism and for its Salafi devotion, its adherence to the first practices of Islam. IS' abuse of online networking and computerized system assumes a key part in its worldwide scattering of promulgation, radicalization, and enlistment. Be that as it may, deliberate research on Islamic fear monger correspondence by means of online networking is constrained. Our examination researches the inquiry: How do IS individuals/supporters utilize Twitter for fear based oppression correspondence: publicity, radicalization, and enrollment? Hypothetically, we drew on microeconomic system speculations to build up a hypothetical structure for multi-sided Twitter organizes in the worldwide Islamic psychological militant corre-spondence condition. Exactly, we gathered 3,039 tweets posted by @shamiwitness who was recognized in earlier research as "a data disseminator" for the IS cause. Methodologically, we performed interpersonal organization investigation, pattern and substance examina-tions of the tweet information. We find solid proof for Shamiwitness-intermediated multi-sided Twitter systems of worldwide broad communications, territorial Arabic broad communications, IS warriors, and IS sympathizers, supporting the structure's utility. The paper will focus on probing solutions that can guide the youth in using Twitter for a more positive approach and how can this influence be eradicated. The interview approach will be used to gather data and make the implications.